Optimizing PEEK implant surfaces for improved stability and biocompatibility through sandblasting and the platinum coating approach - Faadhila, Afrah; Taufiqurrakhman, Mohamad; Katili, Puspita Anggraini; Rahman, Siti Fauziyah; Lestari, Delly Chipta; Whulanza, Yudan (Frontiers in Mechanical Engineering, 2024)
Polyether-ether-ketone (PEEK) stands out as a commonly employed biomaterial for spinal, cranial and dental implant applications due to its mechanical properties, bio-stability and radiolucency, especially when compared to metal alloys. However, its biological inert behavior poses a substantial challenge in osseointegration between host bone and PEEK implants, resulting in implant loosening. Previous studies identified PEEK surface modification methods that prove beneficial in enhancing implant stability and supporting cell growth, but simultaneously, they have the potential to promote bacterial attachment. In this study, sandblasting and sputter coating are performed to address the aforementioned issues as a preclinical work. The aim is to investigate the effects of surface roughness through alumina sandblasting and the platinum (Pt) sputtered coating on the surface friction, cell viability and bacterial adhesion rates in PEEK material. This study reveals that the higher surface roughness average of PEEK sample (the highest was 1.2 μm obtained after sandblasting) increases coefficient of friction which was 0.25 compared to the untreated PEEK of 0.14, indicating more stability performance, but also the bacterial adhesion. A novelty of this study is that the coupled method of Pt-coating after alumina sandblasting is seen to significantly reduce more than 67% of the bacterial adhesion when compared to the sandblasted PEEK sample after 24 hours immersion, implying a better biocompatibility without changing its cell viability performance.